Meritocracy or aristocracy? Appraising the performance appraisal systems. Issue 1 (20th January 2023) - Akhtar, Junaid; Abdullah, Iqra
Abstract : Learning outcomes: The aim of the case is to understand the performance management system of academic staff members in higher education institution. Furthermore, students would be able to compare two performance appraisal policies and analyze which one could better serve the purpose considering the context of educational institution. The case would help students understand the performance dynamics of the academic staff and how the performance management system in place affect employees. Case overview/synopsis: The case study presents a troubling situation faced by Asim Khan, a newly appointed director of the Midland University, regarding retention of the faculty. Upon joining Midland, Khan noticed a trend that faculty who was serving the university from many years are leaving the organization one after the other. He decided to revise the faculty policies that he believed was the root cause of faculty turnover in Midland. He formulated a committee to review the existing policies and revamp if required. The committee identified some flaws in the faculty appraisal policy in place at that time and formulated a new one with the consultation of top management. However, when the new appraisal policy was presented to the faculty, few faculty members raised their eyes over a few aspects of the proposed policy. As the new academic year was approaching, Khan had to make an important decision after critically analyzing the pros and cons of both policies that which of the two should be followed for the upcoming year's appraisals. Complexity academic level: The case can potentially be used in the post-graduate courses in MBA programs offering a major in human resource management. Supplementary materials: Teaching notes are available for educators only. Subject code: CSS 6: Human resource management.